Consensus guideline for the diagnosis and treatment of tetrahydrobiopterin (BH4) deficiencies - Opladen, Thomas; López-Laso, Eduardo; Cortès-Saladelafont, Elisenda; Pearson, Toni S.; Sivri, H. Serap; Yildiz, Yilmaz; Assmann, Birgit; Kurian, Manju A.; Leuzzi, Vincenzo; Heales, Simon; Pope, Simon; Porta, Francesco; et al. (Orphanet journal of rare diseases, 2020)
Tetrahydrobiopterin (BH4) deficiencies comprise a group of six rare neurometabolic disorders characterized by insufficient synthesis of the monoamine neurotransmitters dopamine and serotonin due to a disturbance of BH4 biosynthesis or recycling. Hyperphenylalaninemia (HPA) is the first diagnostic hallmark for most BH4 deficiencies, apart from autosomal dominant guanosine triphosphate cyclohydrolase I deficiency and sepiapterin reductase deficiency. Early supplementation of neurotransmitter precursors and where appropriate, treatment of HPA results in significant improvement of motor and cognitive function. Management approaches differ across the world and therefore these guidelines have been developed aiming to harmonize and optimize patient care. Representatives of the International Working Group on Neurotransmitter related Disorders (iNTD) developed the guidelines according to the SIGN (Scottish Intercollegiate Guidelines Network) methodology by evaluating all available evidence for the diagnosis and treatment of BH4 deficiencies.
Im Text ist "4" tiefgestellt
Gesehen am 23.09.2020